2016
DOI: 10.1007/s10903-016-0464-5
|View full text |Cite
|
Sign up to set email alerts
|

Local-Level Immigration Enforcement and Food Insecurity Risk among Hispanic Immigrant Families with Children: National-Level Evidence

Abstract: Background Local-level immigration enforcement generates fear and reduces social service use among Hispanic immigrant families but the health impacts are largely unknown. We examine the consequence of 287(g), the foundational enforcement program, for one critical risk factor of child health—food insecurity. Methods We analyze nationally representative data on households with children from pooled cross-sections of the Current Population Survey Food Supplemental Survey. We identify the influence of 287(g) on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 29 publications
(65 reference statements)
2
82
0
Order By: Relevance
“…Moreover, passage resulted in temporary increases in enrollment among Latino children with at least one citizen parent. These findings are surprising given two bodies of research: 1) qualitative studies in which parents reported increased barriers to enrolling their children in public benefits after omnibus law passage (Koralek et al, 2009; Quiroga et al, 2014, White et al, 2014b), and 2) studies showing negative effects of local immigration enforcement on public benefits enrollment for children of noncitizens (Potochnick et al, 2016; Vargas and Pirog, 2016; Watson, 2014). …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, passage resulted in temporary increases in enrollment among Latino children with at least one citizen parent. These findings are surprising given two bodies of research: 1) qualitative studies in which parents reported increased barriers to enrolling their children in public benefits after omnibus law passage (Koralek et al, 2009; Quiroga et al, 2014, White et al, 2014b), and 2) studies showing negative effects of local immigration enforcement on public benefits enrollment for children of noncitizens (Potochnick et al, 2016; Vargas and Pirog, 2016; Watson, 2014). …”
Section: Discussionmentioning
confidence: 97%
“…For Latino children with noncitizen parents, heightened state and local immigration enforcement was associated with a reduced probability of enrollment in Medicaid (Pedraza and Zhu, 2013; Watson, 2014) or nutrition assistance programs (Vargas and Pirog, 2016; Watson, 2014) and an increased risk of food insecurity (Potochnick et al, 2016). The enforcement measures studied in these laws are different from omnibus laws in a few important ways.…”
Section: Introductionmentioning
confidence: 99%
“…Excluding counties that have not initiated a 287(g) agreement allows us to compare counties with similar political environment towards undocumented immigrants (Potochnick, Chen, & Perreira, 2016). Further, we also estimate models that do not include any control for the 287(g) request (column 6).…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…suggests that local immigration enforcement increased Latino housing foreclosure rates (Rugh & Hall, 2016) and food insecurity and poverty in vulnerable families with children (Amuedo-Dorantes, Arenas-Arroyo & Sevilla, 2016, Potochnick, Chen, & Perreira, 2016Rugh & Hall, 2016).…”
mentioning
confidence: 99%
“…According to Steckley (2016) and Li and Zhang (2017), food security occurs when the community physically, socially, and economically has continuous access to food that is adequate, safe, and nutritious so that people can meet their food requirements and be healthy and active. In contrast, food insecurity is defined as the inability to obtain sufficient and suitable food for a healthy and active life (Mammen et al 2009;Musemwa et al 2015;Azeem et al 2016;Potochnick 2016;Stephens et al 2017).…”
Section: Introductionmentioning
confidence: 99%